Disturbance-induced phytoplankton regime shifts and recovery of cyanobacteria dominance in two subtropical reservoirs. (1st September 2017) - Yang, Jun R.; Lv, Hong; Isabwe, Alain; Liu, Lemian; Yu, Xiaoqing; Chen, Huihuang; Yang, Jun
Abstract: Many countries in the world still suffer from high toxic cyanobacterial blooms in inland waters used for human consumption. Regional climate change and human activities within watersheds exert a complex and diverse influence on aquatic ecosystem structure and function across space and time. However, the degree to which these factors may contribute to the long-term dynamics of plankton communities is still not well understood. Here, we explore the impacts of multiple disturbance events (e.g. human-resettlement, temperature change, rainfall, water level fluctuations), including six combined disturbances, on phytoplankton and cyanobacteria in two subtropical reservoirs over six years. Our data showed that combined environmental disturbances triggered two apparent and abrupt switches between cyanobacteria-dominated state and non-cyanobacterial taxa-dominated state. In late 2010, the combined effect of human-resettlement (emigration) and natural disturbances (e.g. cooling, rainfall, water level fluctuations) lead to a 60–90% decrease in cyanobacteria biomass accompanied by the disappearance of cyanobacterial blooms, in tandem with an abrupt and persistent shift in phytoplankton community. After summer 2014, however, combined weather and hydrological disturbances (e.g. warming, rainfall, water level fluctuations) occurred leading to an abrupt and marked increase of cyanobacteria biomass, associated with a return to cyanobacteria dominance. These changes in phytoplankton community were strongly related to the nutrient concentrations and water level fluctuations, as well as water temperature and rainfall. As both extreme weather events and human disturbances are predicted to become more frequent and severe during the twenty-first century, prudent sustainable management will require consideration of the background limnologic conditions and the frequency of disturbance events when assessing the potential impacts on reservoir biodiversity and ecosystem functioning and services. Graphical abstract: Highlights: Effects of disturbances on phytoplankton in reservoirs were studied over six years. A decline in cyanobacteria was recorded due to human resettlement and climate change. Cyanobacteria dominance was reestablished following the combined disturbances. Prudent sustainable management of water quality must be based on local conditions.